A COMPARISON OF THE OPINIONS OF THE UNDERGRADUATE STUDENTS' FROM GEOGRAPHY DEPARTMENT AND GEOGRAPHY EDUCATION DEPARTMENT AS REGARDS THEIR FIELD COMPETENCE - Nurcan Demiralp (Informascope, 2017)
Turkish Ministry of National Education established special field competencies for secondary education teachers in 2011. Special field competences are field-specific knowledge, skills, and attitudes necessary for effective and productive conduct of teaching profession. The aim of the present article is to compare the opinions of Geography Education Department, and Geography Department students regarding the field knowledge, one of the special field competences of geography teaching. The study was based on survey method aimed to reveal an existing situation. However, face-to-face interviews were conducted with 20 students from the Faculty of Education in order to find the origin of results. The study was performed in the spring semester of 2014-2015 academic year with a total of 160 students from 3rd, 4th, and 5th grades of Geography Education Department and 3rd and 4th grades of Geography Department. Significant differences between the opinions of students were compared by Chi- Square analysis by their educational programs. The expressions of Faculty of Education students suggested that they were competent in 7 out of 13 fields, creating a significant difference. There was no significant difference in the opinions of Geography Department students regarding the geography field competences.